Maraknya Tindakan Kriminal Yang Menyalahi Sistem Etika Pancasila - Nabillah Salsabila; Astri Lestari; Azka Najmi Tsaqila; Maulia Depriya Kembara (Pusat Riset dan Inovasi Nasional, 2024)
Pancasila is the regulatory policy of the Indonesian state. Moreover, this is a hypothetical system designed to provide requirements and guidelines on the attitudes and character of Indonesians. This means that society is required to be able to improve its own moral dimension in order to be able to show its attitude towards life as an Indonesian nation. Ultimately, we hope to become a scientific and academic community that can make comprehensive decisions from a moral point of view. Method is the method used to solve the problem of an object being studied. According to Sugiyono, the research method/approach used in this research is a qualitative approach.